Electronic-ionic polymer composite for high output voltage generation. (1st March 2022) - Panwar, Varij; Panwar, Lokesh Singh; Anoop, Gopinathan; Park, Sukho
Abstract: The ionic polymer transducers (IPT) have been widely proposed for actuators, energy harvesting, pressure sensing, and robotics applications owing to their exceptional flexibility and actuation performance. However, IPT sensors have a limitation of low output voltage (<1 V) with bending strain that hampers their application in energy harvesting devices and robotics. To address the issue of low output voltage in IPT sensors, we propose a strategy including the introduction of poly(3, 4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) into a poly(vinylidene-fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TRFE-CTFE)/polyvinylpyrrolidone blend to develop the electronic-ionic polymer composite (EIPC) that exhibits a high output voltage of up to 27 V in ionic liquid (IL) condition. The PVP aids in the formation of 89 nm (nm) PEDOT:PSS crystals, a low contact angle of 53.75°, and pores on the surface of the P(VDF-TRFE-CTFE)/PVP/PEDOT:PSS-based EIPC with a ratio of 10/05/85, resulting in high water uptake (WUP) (0.92), high DC conductivity (σdc ) (0.02 S/cm) and high electrical current 0.02 A/cm 2, which improve the high output voltage (27 V) and output power density (4.05 W/cm 2 ) compared to previous existing PEDOT based composites sensors and IPTs based on P(VDF-TRFE-CTFE)/PVP/ionic liquid, P(VDF-TRFE-CTFE)/PVP/PSSA and Nafion membranes. For wearable sensor application, the EIPC was attached to the index finger of humans and generated 25 V with bending of the finger with an angle of 180°. With high ductile nature (tensile strain 223%) and high output voltage of 27 V with bending strain, the EIPC sensors will find practical applications in strain sensors, wearable devices, and energy harvesting devices. Graphical abstract: Image 1 Highlights: PVP helps generate around 89 nm size PEDOT crystals and pores formation on the surface of the TER/PVP/PEDOT:PSS EIPC. The TER/PVP/PEDOT:PSS EIPCs show high DC conductivity than the previous ionic polymers. The TER/PVP/PEDOT:PSS EIPCs generated 25 V when EIPC was placed on the index finger and bending with 180°. The TER/PVP/PEDOT:PSS EIPC sensors produced 27 V with a bending strain of 0.009 than the existing ionic polymer sensors.